Genes Encoding Aluminum‐Activated Malate Transporter II and their Association with Fruit Acidity in Apple. Issue 3 (1st November 2015) - Ma, Baiquan; Liao, Liao; Zheng, Hongyu; Chen, Jie; Wu, Benhong; Ogutu, Collins; Li, Shaohua; Korban, Schuyler S.; Han, Yuepeng
Abstract : A gene encoding aluminum‐activated malate transporter (ALMT) was previously reported as a candidate for the Ma locus controlling acidity in apple ( Malus × domestica Borkh.). In this study, we found that apple ALMT genes can be divided into three families and the Ma1 gene belongs to the ALMTII family. Duplication of ALMTII genes in apple is related to the polyploid origin of the apple genome. Divergence in expression has occurred between the Ma1 gene and its homologs in the ALMTII family and only the Ma1 gene is significantly associated with malic acid content. The Ma locus consists of two alleles, Ma1 and ma1 . Ma1 resides in the tonoplast and its ectopic expression in yeast was found to increase the influx of malic acid into yeast cells significantly, suggesting it may function as a vacuolar malate channel. In contrast, ma1 encodes a truncated protein because of a single nucleotide substitution of G with A in the last exon. As this truncated protein resides within the cell membrane, it is deemed to be nonfunctional as a vacuolar malate channel. The frequency of the Ma1Ma1 genotype is very low in apple cultivars but is high in wild relatives, which suggests that apple domestication may be accompanied by selection for the Ma1 gene. In addition, variations in the malic acid content of mature fruits were also observed between accessions with the same genotype in the Ma locus. This suggests that the Ma gene is not the only genetic determinant of fruit acidity in apple.